(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the proportion of mothers with children under 5 years old at Le Van Thinh Hospital clinic in Thu Duc City who have the correct knowledge, positive attitudes, and correct practices on Hand, foot, and mouth disease (HFMD) prevention. Methods: A cross-sectional study was conducted on 304 mothers of children under 5 years old at Le Van Thinh Hospital in Thu Duc City from February to May 2024. Describe qualitative variables using frequencies and percentages and test the relationships by Chi-square test or Fisher test with α = 0,05, then estimate the relationships by prevalence ratio (PR) with 95% confidence interval, p-value <0,05. Results: Mothers had the correct knowledge, positive attitudes, and good practices about HFMD prevention reaching 9,5%, 59,5%, and 52% respectively. There is a relationship between general knowledge and characteristics of education levels, occupation, economic conditions, and children’s history of HFMD. Conclusion: The proportion of mothers with correct knowledge, positive attitudes, and practices is low. It is necessary to continue health education communication to improve knowledge, attitudes, and practices of HFMD prevention for mothers to reduce the incidence of this disease in children.